2019
DOI: 10.3390/ijms20030588
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Contradictions of Metal Nano-Particle Applications for Radio-Sensitivity Enhancement in Cancer Therapy

Abstract: From the very beginnings of radiotherapy, a crucial question persists with how to target the radiation effectiveness into the tumor while preserving surrounding tissues as undamaged as possible. One promising approach is to selectively pre-sensitize tumor cells by metallic nanoparticles. However, though the “physics” behind nanoparticle-mediated radio-interaction has been well elaborated, practical applications in medicine remain challenging and often disappointing because of limited knowledge on biological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 80 publications
1
49
1
Order By: Relevance
“…Consistent with our findings, AGuIX gadolinium nanoparticles also intensified DSB occurrence in head and neck tumor cells exposed to carbon ion irradiation [13]. In contrast, Gd-, Pt-, and Au-based nanoparticles approximately 2–3 nm in size all made no difference to the DSB occurrence under γ-rays, as newly reported by Pagáčová [41]. In our previous study, we also found that cotreatment with GONs and X-ray irradiation failed to induce more serious DSBs than that observed with irradiation alone [42].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, AGuIX gadolinium nanoparticles also intensified DSB occurrence in head and neck tumor cells exposed to carbon ion irradiation [13]. In contrast, Gd-, Pt-, and Au-based nanoparticles approximately 2–3 nm in size all made no difference to the DSB occurrence under γ-rays, as newly reported by Pagáčová [41]. In our previous study, we also found that cotreatment with GONs and X-ray irradiation failed to induce more serious DSBs than that observed with irradiation alone [42].…”
Section: Discussionsupporting
confidence: 91%
“…In another study, DSBs did not increase for either kV or MV energies with GNPs (Jain et al, 2011). In a thorough study of DNA damage and repair across multiple cell lines and for three different nanoparticles, Pagáčová et al (2019) found that the nanoparticles generally had no effect on enhancing foci. Increases in cell killing in combining radiation with nanoparticles measured through clonogenicity or proliferative ability can be confirmed, yet this does not always correlate with increased DNA damage.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…Gy and fixed at different periods of time post-irradiation. given conditions and various cell types [14][15][16]18,20,28,34,40,41,76,88,89].…”
Section: Methods Verification and Practical Applicationsmentioning
confidence: 99%
“…Imprecise DSB repair then causes mutagenesis and may lead to cancer [7,12]. DSB damage induction and repair monitoring thus opens the doors to personalized medicine [3,4,[13][14][15], for instance, coupled with direct radiotherapy effect monitoring [13,16], and rational development of new DNA damaging [17][18][19][20] or protecting drugs [21][22][23][24] needed in medicine [25,13,16] and radiation protection [26,27]. Precise and automated DSB damage monitoring is also irreplaceable in biodosimetry [26][27][28][29][30], for instance in situations related to mass radiation accidents (terrorist attacks with radioactive materials) or space exploration where astronauts would be exposed to a mixed field of different radiation types [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%